PENGEMBANGAN BASIC TRAINING FUTSAL PADA GURU PENDIDIKAN JASMANI TINGKAT SEKOLAH MENENGAH ATAS - Dicky Hendrawan; Ratna Dewi (Universitas Negeri Medan, 2020)
Abstract : Development of Futsal Basic Training for High School Level Physical Education Teachers. The purpose of this study was to obtain the basic concept of futsal training for physical education teachers in improving the competence of the futsal sport, so that it could have an impact on school development by obtaining school performance in sports. The development of the Futsal Basic Training is an effort to increase the role of teachers to contribute to developing schools with achievements. The achievement is done by the physical education teacher's ability to give confidence to the school in their abilities. The research stages for the development of basic futsal training are to use a research and development design through Intructional design with the ADDIE approach (analysis, design, development, implementation, and evaluation). The results showed that the development of basic training in futsal at the high school level has basic basic elements, namely physical aspects and skills aspects. Physical aspects include cardiovascular endurance, speed, and agility. The skill aspect includes passing and dribbling. The concept developed as a basic component of futsal training shows that the category is very good. The performance aspect was 96.7%, the assessment aspect was 92%, and the effectiveness aspect was 96%. The overall assessment shows that basic futsal training products greatly contribute to developing training programs and determining students who have basic futsal talents that can be developed. Basic training products can be implemented in futsal extracurricular activities in the high school education unit.Keywords : Basic_Training; Futsal; Physical educationAbstrak : Pengembangan Basic Training Futsal Pada Guru Pendidikan Jasmani Tingkat Sekolah Menengah Atas. Tujuan penelitian ini adalah untuk memperoleh konsep basic training futsal pada guru pendidikan jasmani dalam meningkatkan kompetensi cabang olahraga futsal, sehingga dapat berdampak pada pengembangan sekolah dengan perolehan prestasi sekolah bidang olahraga. Pengembangan Basic Training Futsal merupakan upaya peningkatan peran guru untuk berkontribusi mengembangkan sekolah dengan prestasi. Perolehan prestasi dilakukan kemampuan guru penjas dalam memberikan kepercayaan kepada sekolah terhadap kemampuan yang dimiliki. Tahapan penelitian pengembangan basic training futsal adalah dengan menggunakan desain penelitian pengembangan atau research and development (RnD) melalui Intructional design (desain pembelajaran) dengan pendekatan ADDIE (analysis, design, development, implementation, dan evaluation). Hasil penelitian menunjukkan bahwa pengembangan basic training cabang olahraga futsal tingkat sekolah menengah atas (SMA) memiliki unsur basic baku yaitu aspek fisik dan aspek keterampilan. Aspek fisik meliputi daya tahan kardiovaskular, kecepatan, dan kelincahan. Aspek keterampilan meliputi passing dan dribbling. Konsep yang dikembangkan sebagai komponen basic training futsal menunjukkan kategori sangat baik. Aspek penampilan dengan persentase 96,7%, aspek penilaian 92%, dan pada aspek penilaian efektifitas 96%. Keseluruhan penilaian menunjukkan bahwa produk basic training futsal sangat berkontribusi dalam mengembangkan program latihan dan penentuan siswa yang memiliki talenta (basic) futsal yang dapat dikembangkan. Produk basic training dapat diimplementasikan pada ekstrakurikuelr futsal pada satuan pendidikan Sekolah Menegah Atas (SMA).Kata Kunci : Basic_Training; Futsal; Pendidikan_Jasmani